Development of cassava peeling machine using an abrasive mechanism - Alhassan, Elijah Aina; Ijabo, Oga Joshua; Emmanuel, Afolabi (Journal of Production Engineering, 2023)
Cassava, a household name in Nigeria because of its importance in the food supply matrix of the populace. A multipurpose crop that serves as source of food for man, animals and raw materials for industry. The need to appropriate the enormous potentials inherent in cassava necessitated the development of an abrasive cassava peeling machine. The machine consists of the process, support and control unit and it evaluation was based on the effect of drum fill and residence time on performance indices investigated. The machine performed well when operated at reduced speed achieved by using a reduction gear to obtain 74% highest peeling efficiency, 31 kg/hr machine capacity and 5% minimum flesh loss for 10-50% drum fill and 20-30 minutes residence time.